Trypanotolerance, an option for sustainable livestock production in areas at risk from trypanosomiasis - D'Ieteren, G.D.M.; Authié, Edith; Wissocq, N.M.; Murray, M. (World Organisation for Animal Health, 1998)
Trypanosomosis is one of the major constraints on animal production in areas of Africa which have the greatest potential for significant increases in domestic livestock populations and livestock productivity. While the eradication of trypanosomosis from the entire continent is an unrealistic goal, considerable effort has been invested in the control of this disease through the use of trypanocidal drugs, management of the vector and exploitation of the genetic resistance exhibited by indigenous breeds. There is little hope that a conventional, anti-infection vaccine will be produced in the near future. Drug resistance is developing faster than generally thought. The control of the tsetse fly has been attempted over many decades. The decreasing efficacy of available trypanocidal drugs and the difficulties of sustaining tsetse control increase the imperative need to enhance trypanotolerance through selective breeding, either within breeds or through cross-breeding. Trypanotolerance has been defined as the relative capacity of an animal to control the development of the parasites and to limit their pathological effects, the most prominent of which is anaemia. A major constraint on selection for trypanotolerance in cattle, for both within-breed and cross-breeding programmes, has been the absence of practical reliable markers of resistance or susceptibility. Distinct humoral immune response to trypanosome infection is the major feature of bovine trypanotolerance. The role that these responses play in the control of infection or disease is being addressed by ongoing research, but remains a matter of speculation at present. Results in recent years have shown that packed cell volume (PCV) in particular and parasitaemia, the two principal indicators of trypanotolerance, are strongly correlated to animal performance. However, although direct effects of trypanosome infections of PCV and growth are obvious, more sensitive diagnostic methods for reflecting parasite control are required so that individual animals can be categorised reliably for their parasite control capability. One key finding is the major contribution made by each of the indicators evaluated to the overall trypanotolerance variance. Preliminary genetic parameters for PCV provide evidence that trypanotolerance is not only a breed characteristic but is also a heritable trait within the N'Dama population; this brings new opportunities for improved productivity through selection for trypanotolerance. More reliable estimation of genetic parameters of the indicators may well show that these parameters must be handled simulateneously for optimal progress. This would require diagnostics for assessing parasite control capability that identify trypanosome species more accurately, especially in mixed infections. A major advantage of trypanotolerant livestock, particularly N'Dama cattle, is the resistance or adaptation of this breed to many of the important pathogens which prevail in the sub-humid and humid tropics. Research on practical indicators of resistance to these conditions will be required to establish relevant integrated strategies based on disease-resistant livestock. Selective breeding will require the integration of the traits that farmers hold important for their production systems.